Model Gender Interacts With Expressed Emotion to Enhance Startle: Angry Male and Happy Female Faces Produce the Greatest Potentiation - Åsli, Ole; Øvervoll, Morten (Frontiers in Human Neuroscience, 2020)
Several studies have implied gender differences in startle reaction to emotional facial expressions. However, to date, no studies have been designed to investigate the difference between responding to various emotional female versus male faces, nor the gender difference in responses. The present experiment investigated startle EMG responses to pictures of neutral, happy, angry, fearful and sad facial expressions presented by female and male models. Participants were divided into female and male groups. Results showed that emotional facial expressions interact with model sex to produce startle potentiation to a probe: Greater responses were found while viewing angry expressions for male models, and while viewing happy faces for female models. These findings underlines the importance of controlling for model gender in research using facial expressions as stimuli.